Evaluating Emotional Intelligence among Library Professionals in Maharashtra Universities (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
This study evaluates emotional intelligence (EI) among library professionals in Maharashtra universities, specifically focusing on five institutions: University of Mumbai, SavitribaiPhule Pune University, Shivaji University, Nagpur University, and North Maharashtra University. Recognizing the importance of EI in enhancing professional effectiveness and managing interpersonal relationships, particularly in service-oriented roles like librarianship, this research employs a mixed-method approach. Quantitative surveys and qualitative interviews are used to assess EI across dimensions such as self-awareness, self-regulation, motivation, empathy, and social skills among a sample of 200 participants. The findings aim to identify gaps in emotional competencies and suggest targeted training and development programs to enhance EI. This research contributes to the understanding of how emotional intelligence can improve workplace dynamics and service quality in academic libraries, fostering a more emotionally adept and responsive workforce.